Population Structure of Double-Stranded RNA Mycoviruses That Infect the Rice Blast Fungus Magnaporthe oryzae in Japan - Owashi, Yuta; Aihara, Mitsuhiro; Moriyama, Hiromitsu; Arie, Tsutomu; Teraoka, Tohru; Komatsu, Ken (Frontiers in Microbiology, 2020)
Various viruses infect Magnaporthe oryzae (syn., Pyricularia oryzae), which is a well-studied fungus that causes rice blast disease. Most research has focused on the discovery of new viruses and the hypovirulence-associated traits conferred by them. Therefore, the diversity and prevalence of viruses in wild fungal populations have not been explored. We conducted a comprehensive screening of M. oryzae mycoviruses from various regions in Japan using double-stranded RNA electrophoresis and RT-PCR assays. We detected three mycoviruses, Magnaporthe oryzae virus 2 (MoV2), Magnaporthe oryzae chrysovirus 1 (MoCV1), and Magnaporthe oryzae partitivirus 1 (MoPV1), among 127 of the 194 M. oryzae strains screened. The most prevalent virus was MoPV1 (58.8%), which often co-infected in a single fungal strain together with MoV2 or MoCV1. MoV2 and MoCV1 were found in 22.7% and 10.8% of strains, respectively, and they were usually distributed in different regions so that mixed-infection with these two mycoviruses was extremely rare. The predominance of MoPV1 in M. oryzae is supported by significant negative values from neutrality tests, which indicate that the population size of MoPV1 tends to increase. Population genetic analyses revealed high nucleotide diversity and the presence of phylogenetically diverse subpopulations among the MoV2 isolates. This was not the case for MoPV1. Furthermore, studies of a virus-cured M. oryzae strain revealed that MoV2 does not cause any abnormalities or symptoms in its host. However, a leaf sheath inoculation assay showed that its presence slightly increased the speed of mycelial growth, compared with virus-free mycelia. These results demonstrate that M. oryzae in Japan harbors diverse dsRNA mycovirus communities with wide variations in their population structures among different viruses.